2005
DOI: 10.1191/0962280205sm410oa
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian designs with frequentist and Bayesian error rate considerations

Abstract: So far, most Phase II trials have been designed and analysed under a frequentist framework. Under this framework, a trial is designed so that the overall Type I and Type II errors of the trial are controlled at some desired levels. Recently, a number of articles have advocated the use of Bayesian designs in practice. Under a Bayesian framework, a trial is designed so that the trial stops when the posterior probability of treatment is within certain prespecified thresholds. In this article, we argue that trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…Several similar approaches of taking the Bayesian framework to achieve good frequentist properties have been proposed in the literature. [43,44] We advocate the use of extensive computation and/or simulation studies to search for the optimal design parameters and to evaluate the design's operating characteristics. Sensitivity analysis should be conducted to examine how the design parameters influence the design properties.…”
Section: Discussionmentioning
confidence: 99%
“…Several similar approaches of taking the Bayesian framework to achieve good frequentist properties have been proposed in the literature. [43,44] We advocate the use of extensive computation and/or simulation studies to search for the optimal design parameters and to evaluate the design's operating characteristics. Sensitivity analysis should be conducted to examine how the design parameters influence the design properties.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of them are extensions in a randomized fashion of popular single-arm designs for phase II of clinical trials based on a frequentist approach (see the textbook by Jung, 2013, for a review). The development of randomized versions of Bayesian single-arm two-stage designs previously proposed (see, for instance, Tan and Machin, 2002;Wang et al, 2005;Sambucini, 2010) could be an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…This study was also used by Tan and Machin [9] and Wang et al [12] to illustrate their Bayesian designs. In the original trial, the number of patients to be enrolled in the two stages was found using the Simon's minimax design.…”
Section: An Illustrative Examplementioning
confidence: 95%